2019
DOI: 10.1038/s41598-019-54362-0
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol metabolism in pregnancies with small for gestational age neonates

Abstract: Small for gestational age (SGA) newborns are often born from hypertensive pregnancies. This study aimed to compare the systemic metabolism of cortisol (F) in pregnancies with SGA and appropriate for gestational age (AGA) infants, considering both the normotensive (NT) and hypertensive patients. We hypothesized that the disturbances in systemic metabolism of F in pre-eclampsia (PE) might be attributed not to hypertension only, but to SGA. The study included 117 pregnants in the third trimester, divided into gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
4
3
0
Order By: Relevance
“…1), while its metabolic ratio relative to cortisol, THF/F, was also higher in women carrying SGA fetus (Fig. 2A), similar to previous ndings in pregnant women in third trimester [13]. Our study demonstrated that these changes may also represent predictive biomarkers in the rst trimester.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…1), while its metabolic ratio relative to cortisol, THF/F, was also higher in women carrying SGA fetus (Fig. 2A), similar to previous ndings in pregnant women in third trimester [13]. Our study demonstrated that these changes may also represent predictive biomarkers in the rst trimester.…”
Section: Discussionsupporting
confidence: 91%
“…However, the serum levels of cortisol in the SGA group at early stage of the rst trimester were not statistically signi cant (P = 0.337; Fig. 1), consistent with previous studies involving women in the rst and third trimesters [12,13].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, decreased functioning of 11β-HSD2 in SGA infants has only been observed in pregnancies with female fetuses [51]. Recent ndings on sex-speci c differences in systemic glucocorticoid imbalance [52] also strengthen the plausibility of our nding that elevated maternal salivary cortisol increases the risk of SGA among female fetuses only. Likewise, previous research indicated that the effects of depression during pregnancy could have a different impact on the two sexes [53].…”
Section: Discussionsupporting
confidence: 68%
“…Cortisol and cortisone also play a vital role in pregnancy ( 12 ). The high concentration of cortisol from the mother needs to be rapidly converted to its inactive metabolite (cortisone) under the actions of the enzyme hydroxysteroid 11β dehydrogenase type 2 ( 13 ). This enzyme is the key to protecting the fetus’s normal growth.…”
Section: Discussionmentioning
confidence: 99%